2022
DOI: 10.1111/bjd.20890
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid after SARS‐CoV‐2 vaccination: spike‐protein‐directed immunofluorescence confocal microscopy and T‐cell‐receptor studies

Abstract: Dear Editor, Growing evidence suggests that SARS‐CoV‐2 vaccination is associated with a variety of cutaneous reactions, also including autoimmune‐mediated conditions such as autoimmune blistering diseases such as bullous pemphigoid (BP). 1,2 We report new‐onset BP in two patients following the first SARS‐CoV‐2 vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 11 publications
3
38
0
1
Order By: Relevance
“…A close relationship between vaccination and BP onset is difficult to prove considering the extensive vaccination of the adult population during COVID-19 pandemic. However, the recent immunopathological findings by Gambichler et al (17) as well as timing reported across our cohort and published cases support the hypothesis of a causal link between SARS-CoV-2 vaccine and BP development. Further research is warranted to better define the nature of SARS-CoV-2-vaccine-associated immune dysregulation leading to BP.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A close relationship between vaccination and BP onset is difficult to prove considering the extensive vaccination of the adult population during COVID-19 pandemic. However, the recent immunopathological findings by Gambichler et al (17) as well as timing reported across our cohort and published cases support the hypothesis of a causal link between SARS-CoV-2 vaccine and BP development. Further research is warranted to better define the nature of SARS-CoV-2-vaccine-associated immune dysregulation leading to BP.…”
Section: Discussionsupporting
confidence: 88%
“…Our sample size prevents the possibility to reliably compare different treatments. However, most of the subjects were easily controlled with treatment regimens concepted for milder forms of BP (i.e., topical steroids, lowto-moderate doses of systemic corticosteroids, doxycycline), supporting the assumption that the majority of COVID-19 induced BP cases would be non-severe (17,(24)(25)(26). Systemic corticosteroids as well as immunosuppressive adjuvants required to achieve disease control in BP may affect the efficacy of anti-SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A total of 195 articles was retrieved and after the screening, 20 articles were finally included for the review. A total of 35 AIBDs cases (including our case) were found, as shown in Table 1 [7] , [8] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . The sub-epithelial diseases were the most frequent, accounting for 28 cases (80.0%), specifically 26 cases of BP (74.3%) and 2 case of LABD (5.7%).…”
Section: Resultsmentioning
confidence: 99%